Multilayered graphene/ZnFe2O4 hybrid composite: Rational preparation, characterization and superior adsorption of Congo red - Waye Zhang (Veruscript Functional Nanomaterials, 2017)
Multilayered porous hierarchical structure of graphene/ZnFe2O4 hybrids was prepared via in situ hydrothermal growth of ZnFe2O4 nanocrystals within interlayer space of reduced graphene oxide, which demonstrated a high specific area of 117 m2∙g−1 and rational porous structures. Batch adsorption studies showed that the product possesses superior adsorption capacity of dyes such as Congo red from aqueous solution. Adsorption equilibrium and kinetic analysis indicated that the adsorption isotherm was well fitted by Langmuir isothermal model with the maximum adsorption capacity of 404.12 mg∙g−1, and the adsorption kinetics followed the pseudo-second-order kinetic equation. Furthermore, this new product can be magnetically separated and regenerated easily, presenting an effective adsorbent for wastewater purification.